(3eHOC GdJbGVj Ydi OQLJjf aj GdbVGA GdLfGFj (B/ s - (3EHQGgje EHQGgje eMeO YHO GdUeOs; (3eOMJ YHO GdMdje QeVGfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb (B- (3LGeYI GdbGgQI,s, 2014)
(3JJfGhd gPg GdOQGSI (B((3eHOC GdJbGVj Ydi OQLJjf aj GdbVGA GdLfGFj(B): (3hbO GfJXeJ GdOQGSI aj bSejf jSHbgeG ebOeI YGeI(B: (3Ke aUd JegjOj HYfhGf(B: " (3GdJWhQ GdJGQjNj ddeHOC hYehejI JWHjbg (B": (3hjYbHgeG NGJeI(B. (3CeG GdbSe GdChd ef GdQSGdI(B: (3acGf HYfhGf(B: " (3GdJbGVj Ydi OQLJjf cCMO GdeHGOF GdQFjSjI aj JfXje GdbVGA GdLfGFj (B": (3hPdc aj HGHjf(B: (3GdChd JfGhd(B: (3eGgjI GdeHOC hJCUjdg ef GdfGMjJf GdadSajI h GdOSJhQjI(B: (3hGdKGfj JfGhd(B: (3OhQ GdeHOC aj EQSGA bhGYO GdYOGdI GdLfGFjI hVQhQJg(B. (3aj Mjf cGf GdbSe GdKGfj HYfhGf(B: " (3fWGb JWHjb GdeHOC CeGe eMGce GdbVGA GdLfGFj (B": (3eJVefkG gPG GdbSe HGHjf(B: (3JfGhd GdChd(B: (3JWHjb GdeHOC CeGe GdeMGce GdLfGFjI GdYGOj (B: (3hGdKGfj NUU deOi EecGfjI JWHjb GdeHOC CeGe GdeMGce GdLfGFjI GdeJNUUI aj GdJTQjYGJ GdhWfjI(B: (3hcPG JWHjbGJ gPG GdeHOC CeGe GdeMGce GdLfGFjI GdOhdjI(B: (3Ke CYbH Pdc NGJeI GdHMK eJVefI fJGFLg hJhUjGJg s
(3CWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI, cdjI GdMbhb, bSe GdbGfhf GdLfGFi (B2014.s
(3HHdjhLQGajG(B: (3UaMGJ (B490-505. s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFj GdYGes; (3GdYOGdI GdLfGFjIs; (3Mb GdOaGYs; (3GdGSJFfGas; (3GdeMGce GdLfGFjI GdOhdjIs; (3fWGb GdJbGVj Ydi OQLJjfs; (3GdJbGVj Ydi OQLJjfs; (3eHOC GdJbGVj Ydi OQLJjfs; (3GdeMGce GdYGOjIs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs